A Subjective Approach to the Study of Oligopolistic Party Systems - PELIZZO, Riccardo (Institutional Knowledge at Singapore Management University, 2005)
The purpose of this paper is to present a new theory of the cartel party. My argument is straightforward. Assuming that parties are the political analog of firms, that party systems are the political analog of markets, that the shares of the electorate are the political analog of the market shares that firms control, Western European party systems share with oligopolistic markets some structural features. Yet, to know whether Western European party systems resemble oligopolistic markets, we need to know whether Western European party systems are non-competitive political markets exactly in the same way in which oligopolistic markets are not competitive. That is we need to know whether changes in (political) supply are competitive adaptations to changes in demand or not. Hence, to focus on supply is not enough. We need to look at changes in supply relative to changes in demand. Moreover, since voters’ perception of parties’ political offer to the electorate does not simply reflect some objective conditions but is instead mediated by subjective factors (preferences, expectations, ideas, and so on…) I further suggest that the perception of the cartel may not be determined by parties’ objectively oligopolistic practices, but it can simply be based on the perception of oligopolistic behavior, that is on the gap between the electorate’s demands and the market’s perceived supply.